Strengthening The Concept of Religious Moderation for Teenagers Through Short Film - Khotimah, Husnul; Rois, Moh.; Indriyani, Dian; Donasari, Renita (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
The aim of this research is to analyze the existence of short film media in strengthening the concept of religious moderation among teenagers. The research methodology is library research, utilizing various literature sources such as books and relevant articles on the topic. The result shows that teenagers have great potential as agents of religious moderation by maximizing their dual roles, as a producers and consumers of short film. This is supported by various lines, such as (1) diversity of natural resources capable of generating creative ideas in the pre-production process; (2) competent human resources by maximizing artificial intelligence in the production and post-production; (3) government policies both in the education curriculum and through the Ministry of Religion in the RPJMN, and (4) the meaning that includes the four concepts of religious moderation in every film production.